Origins and Factors of the Lithuanian Unarmed Anti-Soviet Resistance during the Second Soviet Occupation - Kareniauskaitė, Monika (Genocidas ir rezistencija, 2011)
The subject of the study in this article is the Lithuanian unarmed anti-Soviet resistance and the factors that determined and supported the resistance during the post-Stalin second Soviet occupation (1953−1990). The study seeks to answer the question why, after the destruction of the armed resistance in occupied Lithuania and reconciliation with the inevitability of Soviet rule by the majority of its people, did the aspiration of some Lithuanian people, despite possible reprisals, to fight the occupational authority using peaceful methods, not fade during the entire period of the occupation. The author sought to determine the origins as well as the social and political inspirations of the unarmed anti-Soviet resistance movement and to discuss the dissemination of the ideas of the movement.The Lithuanian unarmed anti-Soviet resistance could be compared to a river, which began with partisan warfare. The essential twist that changed the direction of the current of the river was the Russian dissident movement, whereas the various currents of the Lithuanian unarmed resistance were tributaries of the river. The partisan warfare laid the foundation for the Lithuanian unarmed resistance. It helped to enhance methods for the dissemination of the ideas of the resistance, which led to the emergence of an alternative source of information in Lithuania along with Soviet propaganda. The partisan warfare also passed on the idea of Lithuania as a national state nurtured in 1918−1940 to future generations of Lithuanians and preserved the historical memory. Meanwhile, the Russian dissident movement gave a new form to the lurking desire of Lithuanian society to resist the Soviet system. It moved the Lithuanian unarmed resistance to a more universal track and filled the ideology of the resistance with the struggle for human rights in addition to the wish to restore the state of Lithuania, foster national culture, and combat restrictions on religion. The movement of Russian dissidents encouraged development of such new techniques of unarmed resistance in Lithuania as the writing of petitions and bringing the situation beyond the iron curtain to world attention by providing facts. This also made self-publication more active in Lithuania.Direct and indirect reasons for the Lithuanian unarmed anti-Soviet resistance during the second Soviet occupation can be identified. Direct reasons would include the partisan warfare which laid the foundation for unarmed resistance, the Russian dissident movement, the 1956 protests in Poland, the1956 Hungarian revolution, and the1968 Prague Spring as well as the return of political prisoners and deportees to Lithuania. Indirectly, the Lithuanian unarmed anti-Soviet resistance was determined by technological (technical capacities, the tradition of an underground press, and improvement of radio reception), geopolitical (changes in the Catholic Church after the Second Vatican Council, the propagandistic nature of the cold war, Western propaganda breaking through the iron curtain, and the youth counterculture), political (loosening grip of the regime during de- Stalinisation, stagnation period of Leonid Brezhnev, human rights restrictions in the USSR, censorship, political pressure on the Lithuanian Catholic Church and Russification of Lithuanian citizens), historical – determined by memory (former statehood, wellbeing in independent Lithuania, giving prominence to Lithuanian partisan warfare), and socio-economic (dissatisfaction with the socialist lifestyle, search for material wellbeing) reasons.
Keywords: Lithuania; Soviet occupation; civil anti-Soviet resistance; partisans